Perfil genotípico de Staphylococcus aureus e variáveis zootécnicas e climáticas associadas à mastite em vacas mestiças - Cristiane Viana Guimaraes Ladeira (2017)
In the present study three studies in two dairy herds of crossbred cows (Holstein-Zebu ½ and ¾ Holstein-Zebu) were performed and divided into chapters entitled: Association between climate and zootecnical data with the presence of new intramammary infections in crossbred cows (chapter 1); Climate and zootechnical data associated with the occurrence and etiology of mastitis in ½ Holstein-Zebu cows (Chapter 2) and Staphylococcus aureus genotypes isolated from cows with transient and persistent subclinical and clinical intramammary infections in two Brazilian crossbred dairy herds (Chapter 3). The aim of the first chapter was to identify production and climatic variables associated with the presence of new intramammary infections in crossbred cows ½ and ¾ HZ. The variables parity, the fat and protein (F/P), maximum temperature and relative humidity of the month of collection were significantly associated with new intramammary infections, while milk production was shown to be a protection factor in the herd of ½ HZ cows. In the herd of cows ¾ HZ were considered a risk factor to the variable F/P ratio, unlike the variable parity that was shown to be a protective factor. The most frequent pathogens in both herds were S. aureus, coagulase-negative Staphylococcus and Corynebacterium sp. In the second chapter, production and climatic variables associated with the presence of pathogens causing mastitis and high cellularity in milk of crossbred cows (½ HZ) were identified. The result of this study showed that the variables parity, fat and protein ratio, maximum temperature and relative humidity at the month of sampling collection were risk factors in relation to high SCC. Variables such as milk urea nitrogen, milk production and rainfall at the of sampling were protective factors. Regarding the presence of pathogens, the variables parity, maximum temperature, index temperature and humidity and relative humidity of the month were considered as risk factors and as a protection factor the minimum temperature variable at the month of sampling. In the third chapter, we compare Staphylococcus aureus genotypes from transient and persistent subclinical and clinical intramammary infections in two crossbreed dairy herds. A total of 124 samples were evaluated using the technique of Pulsed Field Gel Electrophoresis (PFGE). The majority of bovine mastitis cases were related to five predominant pulse types (A, G, I, K e B) and to three subtypes A1, G2 e A9. The identification of the factors that improve the risks of mastitis and the epidemiological determination of S. aureus allow effective measures to control this disease.